ANALISIS KINERJA PEGAWAI PADA PT. BANK LAMPUNG KANTOR CABANG PEMBANTU KARTINI - Santi - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
In addition to promotions, other factors that allegedly have an impact on employee performanceare mutations. This research was conducted at PT. Bank Lampung, Branch Office Kartini. The results ofthis study indicate that the partial promotion of position and mutation affect the performance of theemployees at PT. Bank Lampung, Branch Office Kartini.By using F test and the level of significance using 0.05, it obtained F arithmetic amounted to43.353. Because F arithmetic > F table, it can be concluded that jointly promotion positions andmutations have a significant effect on employees performance of PT. Bank Lampung, Branch OfficeKartini.